MSWordSST – A New Steganalytical Tool for Microsoft Word Documents - Stojanov, Ivan; Mileva, Aleksandra; Stojanov, Done; Stojkovich, Natasha (My University, 2020)
Text steganography is the art of hiding data in the text messages or text documents, so that no one suspects it exists. As opposite, the basic task of steganalysis is to detect which carriers have secret bits encoded in them. In this paper, we present a new software tool for steganalysis of nine different format-based steganographic methods in MS Word documents. First, we describe the detection features that we use, which are extracted from the examined document, and after that, we perform experiments for performance analysis of the tool on the legitimate documents and generated stego documents obtained by four property coding methods.
Keywords: Text steganalysis, Open space method, Property coding, Character coding, Invisible characters